2016
DOI: 10.1080/17445647.2016.1195296
|View full text |Cite
|
Sign up to set email alerts
|

Use of isochrone maps to assess the impact of high-speed rail network development on journey times: a case study of Nanjing city, Jiangsu province, China

Abstract: It is well known that the increasing development of transport infrastructure will result in temporal and spatial convergence. As an important component of China's high-speed rail (HSR) network, an ambitious HSR building program in Jiangsu province will extend the network to cover all cities and 95% of counties by 2030. This study aims to present and analyze the impacts of the evolving HSR network in Jiangsu province over the period of 2010-2030 by developing multi-phased isochrone maps of Nanjing city (the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Furthermore, many patients have a wait‐and‐see attitude; that is, they wait rather than search for information on their own or even use m‐health. The reason behind the lack of interest in m‐health information included a lack of trust in m‐health services, which may be related to the uneven quality of existing m‐health service procedures, incomplete data, unsafe data storage and many other problems (Wang et al, 2016 ). The results showed that although the use of smartphones has become quite common, people with cancer are more likely to communicate face‐to‐face with medical staff to obtain information, and this trend is especially common among older patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many patients have a wait‐and‐see attitude; that is, they wait rather than search for information on their own or even use m‐health. The reason behind the lack of interest in m‐health information included a lack of trust in m‐health services, which may be related to the uneven quality of existing m‐health service procedures, incomplete data, unsafe data storage and many other problems (Wang et al, 2016 ). The results showed that although the use of smartphones has become quite common, people with cancer are more likely to communicate face‐to‐face with medical staff to obtain information, and this trend is especially common among older patients.…”
Section: Discussionmentioning
confidence: 99%
“…The cost raster, which is crucial for determining the shortest travel time, is a raster dataset that defines the cost of traveling through each raster cell (Chang, 2012). Since both railways and expressways are closed systems in which stations serve as access and egress points for the transport network, the least-cost path algorithm cannot be directly applied to the closed expressways and railways (Wang et al, 2016). Therefore, a spatially stratified method was introduced to modify the least-cost path algorithm.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…The accessibility of cities in China has improved greatly in recent years due to the rapid development of transport infrastructure. As a result of the increasing availability of high-resolution datasets and the development of spatial analytical methods in GIS, a growing number of researchers have evaluated the spatial accessibility of cities in China, at the national scale (Cao et al, 2013;Jin et al, 2017) or regional scale (Hou & Li, 2011;Wang, Liu, Liu, Sun, & Huang, 2016;Zhang & Lu, 2007). At the national scale, some studies have focused on the effect of a single type of transport infrastructure on city accessibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…can be reached within a given time budget. This information is often represented on a map by isochrones [4], which are lines enclosing areas of equal travel time to or from the given target or set of targets. Another popular representation is a choropleth map showing for each location how long it takes to get to the nearest target [5].…”
Section: Introductionmentioning
confidence: 99%